2023
DOI: 10.1021/acsami.2c18598
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Size and Charge of Carbon Quantum Dots on Their Corneal Penetration and Permeation Enhancing Properties

Abstract: Reaching the corneal endothelium through the topical administration of therapeutic drugs remains a challenge in ophthalmology. Besides, endothelial cells are not able to regenerate, and diseases at this site can lead to corneal blindness. Targeting the corneal endothelium implies efficient penetration through the three corneal layers, which still remains difficult for small molecules. Carbon quantum dots (CQDs) have demonstrated great potential for ocular nanomedicine. This study focuses on the corneal penetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…1) acts as a natural protection against microorganisms and confers mechanical stability to the eye; it is a highly complex structure made of different Corneal stroma is a highly hydrophilic tissue allowing the diffusion of hydrophilic drugs up to 500 kDa layers. 26 The cornea, a transparent and avascular tissue with an average thickness of 500 mm in humans consists of several layers: (i) the corneal epithelium consisting of flattened superficial cells, wing cells, and columnar basal cells, (ii) Bowman's layer, (iii) the corneal stroma, (iv) the Descemet's membrane and (v) the corneal endothelium. Drug delivery is restricted in the cornea due to the presence of intercellular TJs between epithelial and endothelial cells, completely hindering the diffusion of macromolecules via the paracellular route.…”
Section: Corneal Barriersmentioning
confidence: 99%
“…1) acts as a natural protection against microorganisms and confers mechanical stability to the eye; it is a highly complex structure made of different Corneal stroma is a highly hydrophilic tissue allowing the diffusion of hydrophilic drugs up to 500 kDa layers. 26 The cornea, a transparent and avascular tissue with an average thickness of 500 mm in humans consists of several layers: (i) the corneal epithelium consisting of flattened superficial cells, wing cells, and columnar basal cells, (ii) Bowman's layer, (iii) the corneal stroma, (iv) the Descemet's membrane and (v) the corneal endothelium. Drug delivery is restricted in the cornea due to the presence of intercellular TJs between epithelial and endothelial cells, completely hindering the diffusion of macromolecules via the paracellular route.…”
Section: Corneal Barriersmentioning
confidence: 99%
“…Using confocal microscopy, the presence of nanoparticles in the cornea was determined. Monitoring the intensity of fluorescence in the full-thickness cornea allowed for the detection of particle penetration in various layers of the cornea . It could be demonstrated that positively charged spermidine-derived carbon quantum dots (CQDs) were able to penetrate the corneal epithelium and reach the deepest layer of the cornea, the endothelium.…”
Section: Novel Ex Vivo Modelsmentioning
confidence: 99%
“…114 More recently, our research group used an ex vivo bovine whole-eye model (Figure 12B) for corneal penetration studies of nanoparticles, in conjugation with confocal microscopy. 160 Fresh bovine eyes were collected at a local slaughterhouse and transported in a cold, CO 2 -independent medium. The cornea was prepared for analysis by cleaning the whole bovine eye and removing excess tissue.…”
Section: Novel Ex Vivo Modelsmentioning
confidence: 99%
See 2 more Smart Citations